Complement Factor H Inhibits Anti-Neutrophil Cytoplasmic Autoantibody-Induced Neutrophil Activation by Interacting With Neutrophils - Chen, Su-Fang; Wang, Feng-Mei; Li, Zhi-Ying; Yu, Feng; Chen, Min; Zhao, Ming-Hui (Frontiers in Immunology, 2018)
Our previous study demonstrated that plasma levels of complement factor H (FH) were inversely associated with the disease activity of patients with anti-neutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV). In addition to serving as an inhibitor of the alternative complement pathway, there is increasing evidence demonstrating direct regulatory roles of FH on several cell types. Here, we investigated the role of FH in the process of ANCA mediated activation of neutrophils, and neutrophil-endothelium interaction. We demonstrated that FH bound to neutrophils by immunostaining and flow cytometry. Interestingly, ANCA-induced activation of neutrophils, including respiratory burst and degranulation, was inhibited by FH. Although FH enhanced neutrophils adhesion and migration towards human glomerular endothelial cells (hGEnCs), it inhibited ANCA-induced activation of neutrophils in the coculture system of hGEnCs and neutrophils. Moreover, the activation and injury of hGEnCs, reflected by the level of endothelin-1 (ET-1) in the supernatant of cocultures, was markedly reduced by FH. However, we found that FH from patients with active AAV exhibited a deficient ability in binding neutrophils and inhibiting ANCA-induced neutrophil activation in fluid phase and on endothelial cells, as compared with that from healthy controls. Therefore, our findings indicate a novel role of FH in inhibiting ANCA-induced neutrophil activation and protecting against glomerular endothelial injury. However FH from patients with active AAV are deficient in their ability to bind neutrophils and inhibit neutrophil activation by ANCA. It further extends the current understanding of the pathogenesis of AAV, thus providing potential clues for intervention strategies.